Ex Lib[ris] Klaus Rödel [Valerijonas Jucys]. - Jucys, Valerijonas Vytautas (1930-2016) (1971)
Trzy nagie kobiety trzymają otwartą książkę z napisem: Ex Lib Klaus Rödel. Pod wyobrażeniem autograf aut. i data.